2020
DOI: 10.4108/eai.17-12-2020.167656
|View full text |Cite
|
Sign up to set email alerts
|

Detection procedures for Patients of Alzheimer’s Disease using Waveform Features of Pupil Light Reflex in response to Chromatic Stimuli

Abstract: INTRODUCTION: Various studies conducted to predict Alzheimer’s disease (AD) indicate that some pupillight reflex (PLR) features may contain symptoms of the disease. An effective procedure that can predict thedisease using PLRs is needed.OBJECTIVES: Two analytic approaches were examined in order to estimate the possibility of identifying Alzheimer’s patients using features of PLR waveforms from chromatic stimuli. In particular, an index of the probability of being an AD patient is introduced, and the features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The factor scores for blue but not red light pulses were selected once more for use in a regression model, following a stepwise procedure. The dominance of blue light pulses for the prediction was confirmed in a previous study [11], [12]. The possible reason for this may be based on the first hypothesis, which could not be confirmed according to the above evaluation, however.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The factor scores for blue but not red light pulses were selected once more for use in a regression model, following a stepwise procedure. The dominance of blue light pulses for the prediction was confirmed in a previous study [11], [12]. The possible reason for this may be based on the first hypothesis, which could not be confirmed according to the above evaluation, however.…”
Section: Discussionmentioning
confidence: 73%
“…Some typical features are observed such as deviation during the restoration process after the constriction. Several features of waveforms were extracted in order to compare groups of participants in relation to the previous study [12] as shown in Table I. The first hypothesis is that there is a feature difference between the left and right eyes when light pulses are directed at either eye.…”
Section: A Plr Waveformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the level of cognitive activity and mental workload handling ability are often assessed using pupillary changes [2], [3], [4]. The symptoms of AD and aged macular disease (AMD) are also detected using pupillary reactions to the pupil light reflex (PLR) [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%